Uncontrolled diabetes predicts anxiety and depression in CAD patients. (14th October 2021) - Nura, L; Hysein, K; Beqiri, L; Henein, M Y; Bytyci, I
Abstract: Background and aim: Coronary artery disease (CAD) is a major public health problem worldwide because of high incidence of comorbidity and mortality. Diabetes mellitus (DM) is associated with clustered risk factor for CAD. The aim of this study was to assess the impact of diabetes in CAD and its relationship with depression. Methods: The study included 77 patients (mean age 64±11 years, 63% female) with CAD. Based on comorbidity patients were classified into CAD with DM (n=49) and CAD without DM (n=28). In this prospective study demographic, clinic, echocardiographic and angiographic indices were collected as well as scale of anxiety and depression. Results: Patients with CAD and DM were older (p=0.001), had reduced left ventricular ejection fraction-EF (p=0.02), more obese (p=0.03), had higher NYHA class (p=0.04), more prevalent arterial hypertension (p=0.04), and higher anxiety and/or depression scales (p<0.001) compared with patients without DM. Whereas gender was not significantly difference (p=0.11). Diabetes most closely correlated with the scale of depression (r=0.61, p<0. 001). In multivariate analysis, only diabetes OR=1.099 (95% CI 1.028 to 1.231, p<0.001), predicted depression in patients with CAD. Glycemic >8.9 mmol/L, predicted the scale of depression in patients with CAD (sensitivity 75%, specificity 70%, AUC=0.72, p<0.001). Conclusions: Diabetes is the most important risk factor for CAD and the uncontrolled levels are related to patient's disturbed mental health. These results constitute important knowledge for nurses serving CAD patients. Funding Acknowledgement: Type of funding sources: None.